Exploratorium: a potential design solution for the conservation of tropical rainforest - Abdullah, Fadzidah; Ramnan, Nazrin (School of Architecture and Built Environment, Deakin University, and Department of Architecture Kulliyyah of Architecture and Environmental Design International Islamic University Malaysia, 2022)
Forest plays a significant role in maintaining the balance cycle of our ecosystem. It consists of rich biodiversity, which is not only for animals and plants, but also a place for humans to explore and benefit from its resources; such as timber, water, herbs, gold, and oil. The rainforest in Malaysia is believed to be the oldest and has the most biologically diverse forests in the world. However, the Malaysian rainforest is now in danger of disappearing due to deforestation. Thence, there is a need to have an architectural solution to protect the natives’ economic resource and cultural identity. This research has the objectives to examine the problem of deforestation and to explore the potential of architectural design in solving the rainforest conservation issues. This research is conducted using qualitative approach, where data is collected by utilizing the methods of table-research and case study. The proposed architectural solution comes in the form of an Exploratorium, integrated with a research centre. This proposed facility, with its series of forest discovery spaces, would create awareness among the public on the significance of preserving the rainforest; encourage the public to experience the tropical rainforest ecosystem, and let the public to understand the culture of the native communities.